Cracks monitoring and resistivity test for a double-storey house due to cavity in the soil - Shamsudin, M. M. H.; Hamid, N. H.; M Sidek, M. N.; T Aziz, T.I.S.; Awang, H. (Horizon Research Publishing, 2021)
This paper presents the feasibility study of structural assessment and monitoring of two-story house due to soil settlement which was not well-compact before construction commenced. Two stages assessments were conducted to monitor and evaluate the structural integrity of existing double-story house which involves preliminary investigation and detailed assessment. Preliminary investigation includes visual inspection of cracks, soil settlement and structural damages. Meanwhile, detailed assessment comprises of crack width measurement, Non-Destructive Test (NDT) and resistivity test. The first detail assessment was carried out on 18th July 2019 which involved crack width measurement, Ultrasonic Pulse Velocity (UPV) test and rebound hammer test. The second inspection was conducted on 19th October 2019 to monitor and identify the integrity of the structure and the main causes of the problem. Visual inspection and non-destructive test indicate that the defects found in the house can be categorized as partial damage due to soil settlement. Resistivity test showed that there were cavities and void areas underneath the house and during raining season these void areas were filled with water. The soil underneath the house consists of clay, sand, alluvium and limestone. Results from rebound hammer and Ultrasonic Pulse Velocity (UPV) during the monitoring works showed that low compressive strength and poor quality of concrete were developed, respectively. Besides that, monitoring crack width using veneer caliper showed that the crack was active and extended in a short period of time. Therefore, it is recommended to fill up the void area underneath the house with self-compacting concrete in order to control the cracks and structural damages of double-story house.